The Bank of Amsterdam through the lens of monetary competition - Stephen Quinn; William Roberds (Federal Reserve Bank of Atlanta, 2012)
In 1683 the Bank of Amsterdam introduced a form of fiat money that successfully competed with the coinage of the time. We argue that the principal motive for this monetary innovation was the uncertain value of coins circulating within the Dutch Republic. The Bank's fiat money regime persisted until the downfall of the Dutch Republic in 1795 and incorporated modern features such as gross settlement of financial obligations, open market operations, central bank repurchase agreements (the equivalent thereof), and emergency liquidity facilities.
Keywords: E42; E58; N14; 330; fiat money; central bank; monetary competition